Efektivitas Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Dalam Penanganan Kasus Kekerasan Pada Anak Di Kabupaten Merauke, Provinsi Papua Selatan - Wa Ode Sitti Mardiana; Cornelia Evelin Cabui (PAPSEL RESEARCH AND CONSULTANT, 2025)
Child violence is an inappropriate action in child upbringing. Violence includes actions that endanger the health and peace of children, resulting in physical injury or mental pressure on children. To prevent and address violence, mistreatment, exploitation, and neglect of children, a child protection system exists in Indonesia. This study aims to determine the effectiveness of the Women Empowerment and Child Protection Agency in handling cases of child violence in Merauke Regency of South Papua Province. The research method used is qualitative, aiming to provide a general overview as a type of data collected from the field objectively with a phenomenological type. The results show that the effective of the Child Protection Agency in handling cases of child violence in Merauke Regency of South Papua Province is fully implemented optimally according to the effectiveness indicators which states that there are three indicators influencing effectiveness achievement: goal achievement, integration, and adaptation. The supporting factors are activeness and communication of employees, the intetnal environment is condusive to the counselor’s concern for clients however, the obstacle to the effectiveness of intensive mentoring is the finding of inadequate mentoring, client administration professionals who come from outside the region and there are no rewards for carrying out the handling. Keywords : effectiveness, handling child violence, Merauke Regency